KAJIAN TERHADAP IMPLEMENTASI BALANCED SCORECARD DI PERPUSTAKAAN UMUM DAN PERPUSTAKAAN KHUSUS DI INDONESIA - Muthia Nurhayati (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
In the current era of bureaucratic rform, the library as a unit that support the goals of the parent institution is required to produce optimal performance, then how should the performance measurrement at a special library in the ministry/LPNK be done? Balanced scorecard (BSC) is one of management tools that only measures performance on its development. The implementation of BSC is implemented in libraries as general and how BSC is implemented in special libraries in Indonesia. The research method used was descriptive as an effort to show the implementation of BSC with data collection obtained mainly through literature studies on some previous research about BSC implementation in libraries and also through interviews. The research result show that the implementation of BSC on libraries has long been applied outside Indonesia, especially in university libraries, while the implementation of BSC in special libraries in Indonesia remind dependent the sense of the still joining the implementation of BSC of the parent institution.